Cover Feature: Molecule‐Based Transistors: From Macroscale to Single Molecule. (Chem. Rec. 6/2021). Issue 6 (21st June 2021) - Li, Peihui; Jia, Chuancheng; Guo, Xuefeng
Abstract : The cover picture shows the state‐of‐the‐art strategies capable of constructing molecule‐based field‐effect transistors (FETs), whose performance can be achieved by various external controls, through molecular and device design from macroscale to nanoscale and even single molecule. The development challenges of single‐molecule FETs and proposed prospects for further breakthroughs in this field are also discussed. See the Personal Account by P. Li, C. Jia, and X. Guo (DOI:10.1002/tcr.202000114 ).